Electric Ferry Ecosystem for Sustainable Inter-Island Transport in Philippines: A Pilot Study - Palconit, E. V.; Abundo, M. L. S. (Engineering, Technology & Applied Science Research, 2018)
An electric boat system as a pilot study for the electric ferry was designed and field-tested in Samal Island, Philippines, to verify sustainability for inter-island transport. This pilot study uses 4.5m monohull with a displacement weight of 343kg. During the experiment, two cases were compared: in the first case the boat was powered solely with batteries and in the other case with the aid of photovoltaic (PV) modules. For the first case, 24V electric propulsion was driven by two 12V, 100Ah batteries, which resulted to a navigational range of around 18, 16 and 15 trips with energy consumption of 111.64Wh, 117.19Wh and 123.92Wh respectively. In the second case, the photovoltaic modules were attached on the boat to supplement the PV used while on sail. Results in the second case showed that PV module supplemented energy was about to 13.4%, 26.8% and 38.7% using three different speeds like 3.18, 3.32 and 3.84knots and the navigational range extended to 4km, 1km, and 14.4km respectively. Therefore, the electric boat with the aid of PV module answers the problem in the energy management system that deals with the sustainability of the system in the inter-island transport in Philippines.